Influence of Poly-3-hydroxybutyrate Micro-Bioplastics and Polyethylene Terephthalate Microplastics on the Soil Organic Matter Structure and Soil Water Properties - Fojt, Jakub; Denková, Pavla; Brtnický, Martin; Holátko, Jiří; Řezáčová, Veronika; Pecina, Václav; Kučerík, Jiří (Environmental science & technology, 2022)
Adverse effects of microplastics on soil abiotic properties have been attributed to changes in the soil structure. Notably, however, the effects on the supramolecular structure of soil organic matter (SOM) have been overlooked, despite their key role in most soil properties. This work accordingly investigated the influence of plastic residues at various concentrations on the SOM supramolecular structure and soil water properties. To model plastic residues of micro-bioplastics, spherical or spherical-like poly-3-hydroxybutyrate (PHB) was used, while polyethylene terephthalate (PET) was used as a model of conventional microplastics. The results suggest that both types of plastic residues affect SOM properties, including physical stability (represented by water molecule bridges), water binding (represented by decreased desorption enthalpy or faster desorption), and the stability of SOM aliphatic crystallites. The results further showed that the polyester-based microplastics and micro-bioplastics affected the SOM abiotic characteristics and that therefore the observed effects cannot be attributed solely to changes in the whole soil structure. Notably, similar adverse effects on SOM were observed for both tested plastic residues, although the effect of PHB was less pronounced compared to that of PET.